The effect of an acidic stress environment on the stress-intensity factor for GRP laminates - Kawada H.; Srivastava V.K. (My University, 2025)
Experimental results are presented for the direct effect of an acidic stress environment on the stress intensity factor of woven E-glass fibre-reinforced bisphenol-vinylester resin (E-VE), woven E-glass fibre-reinforced bisphenol-epoxy resin (E-ER) and woven C-glass fibre-reinforced bisphenol-vinylester resin (C-VE) composites. Compact type specimens were exposed in hydrochloric acid of various concentrations and temperatures during constant tensile loading conditions. The constant tensile loading tests determined the rate of crack propagation and stress intensity factors for stress-corrosion cracking. The results indicated that the crack propagation behaviour depended on the concentration of acid, temperature, stress-intensity factor and time. However, E-glass fibre composites were more severely damaged by the hydrochloric acid than the C-glass fibre composite, which was confirmed by the fractographic evidence. © 2001 Elsevier Science Ltd. All rights reserved.